Implementasi Networking And Cooperative Dalam Dunia Pendidikan: - Chaira Saidah Yusrie; Ernawati Ernawati; Sofyan Sauri; Faiz Karim Fatkhullah (Jurnal Dirosah Islamiyah, 2021)
Having a Networking or Networking is one very important thing that supports the success of the world of education. As a social being, basically there needs to be socialization or good relations between fellow humans, both in the smallest environment such as household, family, relatives, work colleagues and others. The research that the author uses is a type of literature review research or often called library research, Library Research which is research that is focused on collecting a series of quotations from various books or articles and laws / regulations related to the object of study. The principle of Islam is living together and a person's relationship with society because an individual has limitations. Therefore, the benefits obtained from society are never comparable to the benefits obtained from individuals because of their limitations. Islam instructs its followers in doing jobs to always cooperate with others and when individuals work together and have social relations, the spirit of unity that blows in their anatomy will keep them from being divided, so that Islam places great importance on participation in society. Humans as social beings always need other people. Despite having an adequate life, sufficient intelligence and sufficient physical strength, he will always need an environment where he can share, support each other and work together. Humans need not only religion, science, or entertainment or the arts, but also togetherness. Everything is necessary. Because with religion life is more directed, with knowledge life will be easier, with the art of life more beautiful and with togetherness life will be more useful. Cooperation is the mental and emotional involvement of people in group situations that encourage them to contribute to group goals or various responsibilities for achieving goals. In building a social life, humans create forms of social interaction which are then studied in social science. As members of social groups, we act and behave in certain ways. The behavior of each individual is usually influenced by the behavior of other people which is then known as interaction. The definition of cooperation (cooperative) is an effort made by several people or groups to achieve common goals. This collaboration is an interaction that is very important for human life because humans are social creatures who both need each other. This collaboration can occur when the individual concerned has the same interests and awareness to work together in achieving common goals and interests. Cooperation or collaboration is very important in an organization, as an integral part of efforts to achieve organizational goals. Therefore, the school as an organization needs to continually strive to build a spirit of cooperation for all its members.